Not the Postmenopausal Syndromes, Urinary Complaints are the Most Common Presentation of the Post-Menopausal Women (Faridpur Medical College Journal, 2021)
Postmenopausal estrogen deprived state causes various types of vasomotor symptoms, urogenital symptoms, and long-term health hazards. Among the postmenopausal women, this study was aimed to determine the prevalence of urogenital complaints, epidemiological studies relating with recurrent UTI, and to observe the changing pattern of bacterial resistance to commonly used antibiotics for UTI. This cross-sectional study was conducted in Faridpur, Bangladesh, from January-December 2019. Total 244 postmenopausal women attending the clinic with various complaints were selected as the study population. In-depth history, clinical examination, and relevant investigations were done. Urinary culture and sensitivity were done to isolate the causative organism and to identify the current antibiotic resistance and sensitivity pattern. Among the study population, 94.7% had urinary complaints as their first concern. However, upon query, 85.2% of them revealed that they had other postmenopausal syndromes. Among the study population, 43.4% had recurrent UTI. Burning micturition was the most common (79.2%) urinary complaint. On urinary culture, 57.5% cases had no growth; among the rest, the most common organism was E. coli (19.8%) followed by Proteus (12.3%) and Klebsiella (10.4%). In Proteus and Klebsiella isolates, a high number of resistances for Nitrofurantoin have been found (75% and 66.7% accordingly). Urinary complaints are the most common presentation of postmenopausal women attending the gynecology clinic. They are seeking treatment not to improve the quality of life with hormone replacement therapy (HRT), but getting rid of the pain of recurrent UTI.Faridpur Med. Coll. J. 2020;15(2): 85-91